OPTIMIZATION OF COMMERCIAL SILICA GEL REGENERATION VIA RESPONSE SURFACE METHODOLOGY (ASEAN Engineering Journal, 2024)
Silica gel, a highly porous form of silicon dioxide, is widely used as a desiccant due to its hygroscopic properties and superior characteristics compared to organic materials. Although silica gel can be regenerated and reused, conventional methods often involve prolonged heating and limited ventilation, resulting in energy waste and reduced efficiency. To optimize the regeneration process, this paper presents an experimental approach to regenerate silica gel using response surface methodology (RSM). The study explores the influence of temperature, duration, and natural convection rate, which is regulated by adjusting the vent size of the oven. The results indicate that saturated silica gel at 98-100% equilibrium relative humidity (RH) can be effectively regenerated to nearly its dry weight by applying a temperature of 70°C for a duration of 10 minutes in a cubic oven measuring 15cm on each side, with an approximate vent area of 225cm2. Moreover, assigning different levels of importance to the influencing factors in the Design Expert software allows calibration of these factors to achieve the desired equilibrium RH.